Ethics in corporate America a crisis of credibility - Lehrer, James; Solman, Paul; Toffler, Barbara Ley; Loomis, Carol; Grant, Jim, journalist; Sloan, Allan; Tobias, Andrew P.; Smith, Adam, 1930-; Leonard, Stew, Sr; Andersen, Arthur; Films For The Humanities & Sciences (Firm); Enron Corp; et al. (Princeton, NJ. : Films for the Humanities & Sciences, 2004)
This NewsHour program scrutinizes the state of business ethics in an America riddled with financial fraud. In segment one, correspondent Paul Solman and Columbia Business Schools Barbara Toffler cite Arthur Andersen and Stew Leonard, Sr., as examples of ethics gone awry. Segment two gathers the opinions of veteran business journalists Adam Smith, Carol Loomis, Allan Sloan, Jim Grant, and Andrew Tobias on the practices of Enron, Tyco, Morgan Stanley, and Merrill Lynch. And, after summarizing the evolution of compensation models in the stock analysis industry, segment three examines the conflicts of interest that have led investment stock analysts astray
Originally broadcast on News hour with Jim Lehrer in 2002
Keywords: Business ethics -- United States; Documentary television programs; United States -- Economic conditions -- 2001-